Analysis of selection criteria and the sensitivity of solutions in selecting candidates for a job position - Batinić, Milanka S. (Vojnotehnički glasnik / Military Technical Courier, 2013)
In order to have the best execution of required job tasks, the best task performer should be chosen. The problem of selection of job candidates has been present for long and it was mainly based on empirical estimates and feelings. Multicriteria analysis methods allow a more objective approach to the selection of job candidates. One of these methods is the method of analytical hierarchy process (AHP), which, besides the selection, provides the sensitivity analysis of solutions. This paper considers the criteria for manager selection and analyzes the sensitivity of the obtained solutions with the assumed set of alternatives. Introduction Detailed research and analyses of management and human resource management have led to the following basic principles that need to bi implemented in any organization: - Forming working environment without conflicts where both the employer and the employee have the same goal – the success of the organization. ─ Forming such working environment that motivates employees to work and use their knowledge and skills to the fullest extent, ─ Establishing a balance between the demands of employees and their organization , etc. For the implementation of these principles, the staff structure is essential., It is correlated with the choice of candidates that until now was based mainly on empirical estimates. The lack of objective approaches is now overcome by the application of multicriteria analysis methods. Criteria for the selection of managers The selection of human resources at work is a very complex task. It requires a search for candidates who will meet the requirements of a position with their knowledge, skills and criteria.. The goal function is determined by the choice of criteria for managers and their weight coefficients. On the basis of the analysis of managerial tasks, the criteria for the best candidates have been chosen.. The criteria are divided into: - creativity, - constructiveness, - boldness, - communication, - culture, - cooperation, and - character. Sensitivity analysis of the final solution An important feature of the AHP method is the sensitivity analysis of the final solution using the original software package Ehpert Choice program, which enables testing different sets of alternative solutions. The sensitivity analysis presents related changes in the priorities of alternatives as a function of the importance of attributes or criteria [7]. Dynamic sensitivity analysis This method indicates that a change in the priority of one criterion affects the priorities in other criteria and the priorities of alternatives (candidates) within the observed criterion, as shown in the graph of the dynamic sensitivity analysis (Fig. 3). Gradient sensitivity analysis The gradient analysis (Fig. 4) is used to monitor the impact of changing priorities of one criterion onto the change of priorities of other criteria and alternatives, i.e. onto the final ranking list of alternatives as a aresult. Performance sensitivity analysis This procedure presents the priorities of the criteria and alternatives (candidates) for all criteria taken individually and collectively at the global level and the criteria levels. The significance of the performance sensitivity analysis is in the possibility of determining the final decision ─ alternative ranking for any node in the criteria tree within the respective levels (Fig. 5). Sensitivity analysis head to head This method determines the difference in the significance of one considered criterion in one of the selected pairs of alternatives in relation to the other one, expressed in percentage. A scale below the set of the criteria for which the required value is determined (Fig. 6) is used in the analysis. Two-dimensional sensitivity analysis This analysis shows how alternatives behave according to two criteria and whether the criteria are in conflict (Fig. 7). Conclusion The analysis of the selection criteria and the sensitivity of the obtained solutions in the selection of candidates for managerial positions leads to the following conclusions regarding the fact that the goal of the analysis is to make the selection procedure objective and to facilitate decision-making: ─ selection and description of the criteria for the manager selection open the possibilities for the selection of candidates for any position, ─ the method application procedure is described and the best candidate chosen using a mathematical model, ─ special attention should be paid to determining the weight of criteria and to the knowledge of the true meaning of the criteria, ─ it was determined how the change in the priorities of one criterion affects the change of priorities and criteria of other alternatives, i.e. it is possible to apply an analysis of different versions of approaches to problem solving, ─ mutually conflicting criteria are determined using the software package.